ASYMMETRIC INFORMATION, INVESTMENT OPPORTUNITY, PROFITABILITY, DIVIDEND DAN KEBIJAKAN LEVERAGE PERUSAHAAN MAKANAN MINUMAN - Assegaf, Abdillah (Manajemen Bisnis, 2011)
Gabungan Pengusaha Nasional Angkatan Sungai, Danau & Penyebrangan (GAPASDAP)e-mail: abdillah278@gmail.comABSTRACTPecking order theory is a theory that emphasizes the manager chooses to use retained earnings tofund the company rather than debt and the last alternative new shares issued. This study aims todetermine the influence of asymmetric information, investment opportunity, profitability and dividendon the company?s leverage. Type of data used are secondary data which are reported in the company?sfinancial ratios during the study period in 2006-2009. Results showed that mean of the variableasymmetric information, investment opportunity, profitability and dividend influence simultaneouslyto the leverage of company. There is only asymmetric information which is partially significant toinfluence the company leverage.Keywords: asymmetric information, profitability, investment opportunity, dividend, leverage